Efektivitas Kapal KM Camara Nusantara dalam Pelayanan Angkutan Ternak - Laili Fithri Hidayati; Nahrowi; Luki Abdullah (Institut Pertanian Bogor, 2023)
In 2021, the realization of livestock transported by KM Camara Nusantara livestock ships only reached 67.73%, with the realization of shipping at 78.74%. Based on these conditions, this study aims to measure the effectiveness of implementing livestock ships and the factors that affect them. The method used was to calculate the weight of factors considered to affect using the Analytical Hierarchy Process. Data were obtained from questionnaires, interviews, and literature reviews. Respondents were stakeholders and users of livestock transportation vessel services, which include the NTB and NTT Provincial Livestock Offices, Bima Regency Livestock Office, the Ministry of Transportation, shipping operators, and business actors. The results are priority weights on benefit criteria (0.2648), number of livestock (0.2578), regulation (0.1716), and route (0.1541). Meanwhile, priority weights on the subcriteria of the number of livestock transported (0.2224), availability (0.1064), price disparity (0.0889), mileage (0.0677), and transportation socialization (0.0667). Based on the calculation of the weight of criteria and subcriteria, the effectiveness of implementing KM Camara Nusantara livestock vessels reached 78%, which is at the level of achievement that is quite effective. In general, to improve the effectiveness of KM Camara Nusantara livestock transport ship services, factors that need to get priority are the availability of transported livestock, the achievement of benefits, and supporting regulations. The subfactors that need priority are the number of livestock transported, availability, price disparity, mileage, and transportation socialization. Keywords: AHP, Camara Nusantara, cattle ships, Sea Highway